Complicating connectomes: Electrical coupling creates parallel pathways and degenerate circuit mechanisms. Issue 5 (8th August 2016) - Marder, Eve; Gutierrez, Gabrielle J.; Nusbaum, Michael P.
Abstract: Electrical coupling in circuits can produce non‐intuitive circuit dynamics, as seen in both experimental work from the crustacean stomatogastric ganglion and in computational models inspired by the connectivity in this preparation. Ambiguities in interpreting the results of electrophysiological recordings can arise if sets of pre‐ or postsynaptic neurons are electrically coupled, or if the electrical coupling exhibits some specificity (e.g. rectifying, or voltage‐dependent). Even in small circuits, electrical coupling can produce parallel pathways that can allow information to travel by monosynaptic and/or polysynaptic pathways. Consequently, similar changes in circuit dynamics can arise from entirely different underlying mechanisms. When neurons are coupled both chemically and electrically, modifying the relative strengths of the two interactions provides a mechanism for flexibility in circuit outputs. This, together with neuromodulation of gap junctions and coupled neurons is important both in developing and adult circuits. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 77: 597–609, 2017